CHARACTERISTICS OF THE CHEMICAL COMPOSITION OF OILS OF MODERN SORTES IN LUPIN OF HIGHER EDUCATION AND THE PERSPECTIVES OF USE OF IT IN VARIOUS AREAS OF THE PEOPLE’S AGRICULTURE - Ратошнюк, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The use of fatty acids of lupine oil to create a complete balance of fatty acid composition; antioxidants; vitamins; minerals and other food ingredients is an essential basis for the creation of dietary foods to meet their growing demand from the population. Due to the inclusion of the specified oil in the formulation of food preparation in the amount of 10 % of the weight of fat there is an increase in the proportion of unsaturated and a decrease in the proportion of saturated fatty acids in foods; which is a positive decision and the most effective and economically justifiable method of constructing fat products with a given composition and ratio PUFA; which meets the requirements of the nutrition science. In addition; lupine oil can be an important component in the manufacture of a wide range of articles and products of daily consumption; namely: margarine; mayonnaise; soap; shampoos; lubricants; stearin candles; oils; perfumes; etc.